Relational marketing and CRM in SMEs in the textile and apparel sector in Antioquia - Ruiz-Velásquez, María Andrea; Ceballos, Lina María; Londoño-Vélez, Natalia (Estudios de Administración, 2020)
This qualitative research explores the strategies and activities involved in relationship marketing and Customer Relationship Management (“CRM”) implemented by manufacturing SMEs in the textile and apparel sector in the department of Antioquia, Colombia (South America). The methodology was developed based on 13 in-depth interviews with SMEs in the sector and experts in the fashion industry and relationship marketing. Findings indicate a low level of maturity in the implementation of relationship marketing activities and CRM. Companies with higher levels of maturity had more administrative capacity and employees with higher levels of education, open to technology, with a correct approach to adding value, and open to innovation in terms of processes and services. The lack of marketing guidelines and limited budgets and personnel were the main barriers. The implementation of simple and practical relational marketing plans are recommended to enhance the appropriate use of resources.